PIEZO-ELECTRICALLY DRIVEN THERMOACOUSTIC REFRIGERATOR - V. HARI PRAKASH; P.BHARATH; M. HARI PRASAD (International Journal of Innovations in Engineering Research and Technology, 2021)
The study focuses technically on using the piezo-electric materials to get the desired refrigeration effect. Moreover, the added advantage is that piezo-electrical material replaces the electromagnetic speakers which causes disturbances and expensive too. Finally, the positive outcome of this projectis that the efficiency rate is higher when compared to other refrigeration systems.